REPRESENTASI TOXIC RELATIONSHIP PADA WEB SERIES LAYANGAN PUTUS - Silma Mega Oktaviani; Diana Amalia (Ilmu Komunikasi, FISIP Universitas Pasundan, 2022)
ABSTRACT At the end of 2021, Layangan Putus web series based on the true story of a woman, went viral and was liked by many people. This series also received many awards. Layangan Putus tells the story of a harmonious household life that starts to fall apart with the emergence of a third person, the relationship eventually becomes a toxic relationship. The meaning contained in this series is in sync with the social reality of society nowadays, that makes many people like it. This study aims to determine the representation of toxic relationships in Layangan Putus web series by using descriptive qualitative methods based on Roland Barthes' semiotic theory by examining denotation, connotation and myth. The results of this study indicate that the meaning of denotation in Layangan Putus series is shown through gestures such as diverting eye contact, uncontrolled speech tone, stammering, swearing, yelling, to verbal expressions of love. The meaning of connotation in this study provides an understanding of human behavior that is classified as a toxic relationship, such as lying, verbally and physically violence, to infidelity. The myth in this study shows that a married couple's relationship that was initially fine does not always end happily.